(untitled) (World Economics and Finance Bulletin, 2026)
This article examines the role and importance of the securities market in the process of economic modernization and innovative development. Particular attention is paid to the mechanisms of capital attraction through the stock market, its structure, and development indicators. The study also analyzes financial depth, operations in primary and secondary markets, and key trends in the global financial market.